ANALISIS POTENSI DAN EFEKTIVITAS PAJAK PARKIR DAN RETRIBUSI PARKIR SEBAGAI SUMBER PENERIMAAN PENDAPATAN ASLI DAERAH KOTA SURAKARTA TAHUN 2011 – 2015 - Ganang Ahmad Fathoni, Suharno & Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this study was to analyze the potential and effectiveness of the parking tax and parking fees in the city of Surakarta. Type of this research is a case study. Source data used secondary data such as targets and the realization of income tax and levy revenue from 2011 – 2015. Data were analyzed used the effectiveness test, test and test contribution rate of growth. The results of the analysis concluded that the effectiveness of the parking tax in the years 2011 – 2015 had an average effective rate of 117,38% that declared effective, while the effectiveness of parking fees has a percentage of average effectiveness of 100,43%, so it is declared effective. Analysis of potential parking tax years 2011 – 2015 is said to be growing, although the pace of growth in the years 2011 – 2015 positive contribution this because the parking tax years 2011 – 2015 is less than the average of all contributions of local taxes the years 2011 – 2015 in the amount of 1,52% while the average contribution of local taxes amounted to 13,22%. As for potential parking fees for the years 2011 – 2015 is said to be prima positive growth rate of the years 2011 – 2015 and 2011 – 2015 the contribution potential.Keywords: parking tax, parking fees, effectiveness dan potential matrix.